PENGARUH KERJA SAMA ANTARA ORANG TUA DAN GURU PENDIDIKAN AGMA ISLAM TERHADAP KEMAMPUAN MEMBACA AL-QUR'AN KELAS VI SD INPRES NEGERI NO 230 GARONGGONG - Saharuddin, Saharuddin (Dahzain Nur, 2022)
This study proves that how the effect of cooperation between parents and teachers of Islamic religious education on the ability to read the Qur'an. This study uses Ex Post Facto Quantitative research, namely research that uses numbers while the data collection techniques used are questionnaires and documentation. Questionnaire sheets are question sheets that are distributed to students to find out how students respond to the collaboration of parents and teachers of Islamic education and documentation is used to score sheets on the ability to read the Qur'an for class VI SD Negeri Inpres No. 230 Garonggong. Based on the results of the research conducted, the authors conclude that the collaboration between parents and teachers of Islamic religious education can be seen from the results of the questionnaires distributed with the average number of those who answered Strongly agree 80% agree 20% disagree 0% and strongly disagree 0%. The effect of collaboration between parents and teachers of Islamic religious education There is an influence by looking at the value of the ability to read the Qur'an obtained through teachers in the field of Islamic religious education studies and the ability to read the Qur'an in class VI at SD Negeri No. 230 Inpres Garonggong, namely the results analysis of the number of counts> Percentage Distribution with marked number 3.10> 1.71